2012
DOI: 10.1021/la302779q
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun Nanofibrous Membranes Surface-Decorated with Silver Nanoparticles as Flexible and Active/Sensitive Substrates for Surface-Enhanced Raman Scattering

Abstract: The development of novel nanomaterials with well-controlled morphologies/structures to achieve excellent activities/sensitivities in surface-enhanced Raman scattering (SERS) is crucial in advancing the high-performance SERS detections of chemical and biological species. In this study, amidoxime surface-functionalized polyacrylonitrile (ASFPAN) nanofibrous membranes surface-decorated with silver nanoparticles (Ag NPs) were prepared via the technique of electrospinning followed by the method of seed-mediated ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
111
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(116 citation statements)
references
References 46 publications
3
111
0
Order By: Relevance
“…Flexible plasmonic substrates, such as polymer nanofibers and cellulose paper, are a new class of plasmonic materials with low cost for fast diagnostics 20 . Compared to rigid-substrates, flexible structures are adaptable to a rough substrate in terms of wrapping and bending 21 . Furthermore, flexible plasmonic substrates open the perspective of combination with electronic components to generate a new class of multifunctional devices 22 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Flexible plasmonic substrates, such as polymer nanofibers and cellulose paper, are a new class of plasmonic materials with low cost for fast diagnostics 20 . Compared to rigid-substrates, flexible structures are adaptable to a rough substrate in terms of wrapping and bending 21 . Furthermore, flexible plasmonic substrates open the perspective of combination with electronic components to generate a new class of multifunctional devices 22 .…”
Section: Introductionmentioning
confidence: 99%
“…This approach has been established acquiring Raman signals of analytes adsorbed on 4 polymer nanofibers decorated with silver nanoparticles 28 . To date only few approaches show modification of polymer nanofibers based on in situ growth of plasmonic nanoparticles 21,29 .…”
Section: Introductionmentioning
confidence: 99%
“…Electro-spinning is one of the popular methods for fabricating nanofiber mats, as it can be easily used in the processing of polymers into nanofiber mats by applying a high voltage between the grounding plate (collector) and the spinning nozzle. Several authors have previously reported on fabricated nanofibers covered with metals and conducting polymers [10][11][12], while there are few papers detailing their application to actuators, with the exception of the piezoelectric actuator containing poly(vinylidene fluoride) (PVDF) nanofibers, fabricated using the direct-write electro-spinning technique [13,14]. Among the various conductive nanofibers, PEDOT is a chemically and thermally stable polymer and exhibits a high conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…Considerable effort has been devoted to crafting a host of solid-supported SERS substrates, with results that inspire further efforts to improve and expand fabrication options, sensing capabilities, and sensing performance. 1,3,[7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] Top-down nanofabrication using conventional and unorthodox approaches can produce exquisitely structured substrates, but can require substantial practitioner expertise along with expensive, specialized, and complicated instrumentation, and can moreover substantially limit the palette of fabrication materials. SERS substrates developed outside the material and processing constraints of conventional micro-and nanofabrication have been compelling.…”
mentioning
confidence: 99%
“…17,24,29,33,41,[43][44][45][46][47][48][49][50][51][52] Objects are immersed in liquid baths, with solution access and homogeneity dictating the uniformity of the plating: rough and largearea surfaces can be coated without the geometric-including line-of-sight-constraints of physical vapor deposition. Equipment overhead is minimal, the surface being plated need not be conductive-allowing for support material tolerance-and the plating occurs without the need for external electrical power.…”
mentioning
confidence: 99%